Effect of Agnikarma with Kshoudra over Ankle and Foot in Sciatica due to L4-L5 Intervertebral Disc Prolapse (International Journal of Ayurveda and Pharma Research, 2023)
Sciatica is a syndrome characterized by pain radiating from the low back into the buttock and into the lower extremities along its posterior or lateral aspect and most commonly caused by prolapse of lumbar intervertebral disc. The term is also used to refer the pain anywhere along the course of sciatic nerve. Modern medical practice for sciatica includes oral NSAIDs, opioid and non-opioid analgesics, muscle relaxants, localized corticosteroid injections, physiotherapy and if the above measures fail finally surgery. Sciatica can be correlated with Gridhrasi mentioned under Vata vyadhi in Ayurvedic classics. Various treatment modalities like Snehana, Swedana, Vasthi etc are indicated in Gridharsi. These are very effective treatment procedures but take relatively a more time for pain relief. Agnikarma is very beneficial in painful conditions caused by Vata as it gives immediate relief of pain. Here the patient was treated with Agnikarma using Kshoudra over the tender spots of ankle and foot of affected lower limb. Outcome measures like pain, numbness, tenderness, SLR and ODI were assessed   before treatment, after treatment, 7th day and on 14th day. The result showed that Agnikarma with Kshoudra done over ankle and foot gives immediate relief of pain and numbness of sciatica due to L4-L5 intervertebral disc prolapse.